β€œν™•λ₯ κ³Ό 톡계(MATH230)” μˆ˜μ—…μ—μ„œ 배운 것과 κ³΅λΆ€ν•œ 것을 μ •λ¦¬ν•œ ν¬μŠ€νŠΈμž…λ‹ˆλ‹€. 전체 ν¬μŠ€νŠΈλŠ” Probability and Statisticsμ—μ„œ ν™•μΈν•˜μ‹€ 수 μžˆμŠ΅λ‹ˆλ‹€ 🎲

6 minute read

β€œν™•λ₯ κ³Ό 톡계(MATH230)” μˆ˜μ—…μ—μ„œ 배운 것과 κ³΅λΆ€ν•œ 것을 μ •λ¦¬ν•œ ν¬μŠ€νŠΈμž…λ‹ˆλ‹€. 전체 ν¬μŠ€νŠΈλŠ” Probability and Statisticsμ—μ„œ ν™•μΈν•˜μ‹€ 수 μžˆμŠ΅λ‹ˆλ‹€ 🎲

Theorem.

Let $X$ and $Y$ be independent RVs.

1. Discrete Case

If $X$ and $Y$ are discrete with pmfs $f_X(x)$ and $f_Y(y)$,

then $X+Y$ has the pmf

\[f_{X+Y} (z) = \sum_u f_X(u) f_Y (z-u)\]


2. Continuous Case

If $X$ and $Y$ are continuous with pdfs $f_X(x)$ and $f_Y(y)$,

then $X+Y$ has the pdf

\[f_{X+Y}(z) = \int_u f_X(u) f_Y(z-u) du\]

[2]번 λͺ…μ œμ˜ 경우, 증λͺ…ν•˜λ €λ©΄ μƒλ‹Ήν•œ 엄밀성이 μš”κ΅¬λœλ‹€κ³  μ •κ·œ μˆ˜μ—…μ—μ„œλŠ” [2]λ²ˆμ— λŒ€ν•œ 증λͺ…을 닀루진 μ•Šμ•˜λ‹€.

Proof. [1]

\[\begin{aligned} U &= X \\ V &= X + Y \end{aligned}\] \[f_{U, V} (u, v) = f_{X, Y} (u, v-u) = f_X(u) f_Y(v-u)\]

λ”°λΌμ„œ,

\[f_V (v) = \sum_u f_{U, V} (u, v) = \sum_u f_X(u) f_Y(v-u)\]

$\blacksquare$


Example.

Let $X \sim \text{Gamma}(n, \beta)$, $Y \sim \text{Gamma}(m, \beta)$, and $X \perp Y$.

Find the pdf of $X+Y$.

\[\begin{aligned} f_{X+Y} (Z) &= \int_u f_X (u) f_Y (z-u) \, du \\ &= \frac{1}{\Gamma(n) \cdot \beta^n} \frac{1}{\Gamma(m) \cdot \beta^m} \cdot \int^{\cancelto{z}{\infty}}_0 u^{n-1} e^{-u/\beta} \cdot (z-u)^{m-1} e^{-(z-u))/\beta} \, du \qquad (z - u > 0)\\ &= \frac{1}{\Gamma(n) \cdot \beta^n} \frac{1}{\Gamma(m) \cdot \beta^m} \cdot \int^z_0 u^{n-1} (z-u)^{m-1} \cdot e^{-z/\beta} \, du \\ &= \frac{1}{\Gamma(n) \cdot \beta^n} \frac{1}{\Gamma(m) \cdot \beta^m} \cdot e^{-z/\beta} \cdot \int^z_0 u^{n-1} (z-u)^{m-1} \, du \\ \end{aligned}\]

μ΄λ•Œ, $u = zy$둜 μΉ˜ν™˜μ λΆ„ν•΄λ³΄μž.

\[\begin{aligned} f_{X+Y} (Z) &= \frac{1}{\Gamma(n) \cdot \beta^n} \frac{1}{\Gamma(m) \cdot \beta^m} \cdot e^{-z/\beta} \cdot \int^z_0 u^{n-1} (z-u)^{m-1} \, du \\ &= \frac{1}{\Gamma(n) \cdot \beta^n} \frac{1}{\Gamma(m) \cdot \beta^m} \cdot e^{-z/\beta} \cdot \int^1_0 (zy)^{n-1} (z-zy)^{m-1} \, z dy \\ &= \frac{1}{\Gamma(n) \cdot \beta^n} \frac{1}{\Gamma(m) \cdot \beta^m} \cdot e^{-z/\beta} \cdot z^{n-1} z^{m-1} z \cdot \int^1_0 y^{n-1} (1-y)^{m-1} \, dy\\ &= \frac{1}{\Gamma(n) \cdot \beta^n} \frac{1}{\Gamma(m) \cdot \beta^m} \cdot e^{-z/\beta} \cdot z^{n+m-1} B(n, m) \\ &= \frac{1}{\cancel{\Gamma(n)} \cdot \beta^n} \frac{1}{\cancel{\Gamma(m)} \cdot \beta^m} \cdot e^{-z/\beta} \cdot z^{n-m-1} \frac{\cancel{\Gamma(n)} \cancel{\Gamma(m)}}{\Gamma(n+m)} \\ &= \frac{1}{\Gamma(n+m) \beta^{n+m}} \cdot z^{n+m - 1} e^{-z\beta} \end{aligned}\]

λ”°λΌμ„œ, $X+Y \sim \text{Gamma}(n+m, \, \beta)$인 것이닀! $\blacksquare$

μœ„μ˜ 예제λ₯Ό ν™œμš©ν•˜λ©΄, $\text{Gamma}(n, \beta)$κ°€ $\text{Exp}(\beta)$의 generalizationμž„μ„ μ‰½κ²Œ 확인할 수 μžˆλ‹€.

Let $X_1, \dots, X_n$ follows $\text{Exp}(\beta)$ and they are mutually independent.

We know $\text{Gamma}(1, \beta) = \text{Exp}(\beta)$.

Therefore,

\[(X_1 + \cdots + X_n) \sim \text{Gamma}(n, \beta)\]

not 1-1 Transform

$y = g(X)$ and $g$ is not 1-1

Example.

Let $X$ be a discrete RV with $P(X=0) = P(X=2) = P(X=-2) = 1/3$.

Let $Y := X^2$. Find $f_Y(y)$.

Since $Y = X^2$, $Y = \{ 0, 4\}$

λ”°λΌμ„œ,

(1) If $y=4$, then $x=2$ or $x=-2$

\[P(Y = 4) = P(X^2 = 4) = P(X=2) + P(X = -2) = \sum_{x: g(x)=4} f_X (x) = 2/3\]

(2) If $y=0$, then $x=0$

\[P(Y = 0) = P(X^2 = 0) = P(X=0) = \sum_{x: g(x) = 0} f_X (x) = 1/3\]


Example.

Let $X \sim N(0, 1)$. Find the pdf of $Y := X^2$.

\[\begin{aligned} P(Y \le y) &= P(X^2 \le y) \\ &= P(-\sqrt{y} \le X \le \sqrt{y}) \\ &= P(X \le \sqrt{y}) - P(X \le -\sqrt{y}) \\ &= F_X (\sqrt{y}) - F_X (-\sqrt{y}) \end{aligned}\]

μœ„μ˜ cdf μ‹μ—μ„œ pdfλ₯Ό μœ λ„ν•΄λ³΄λ©΄,

\[\begin{aligned} f_Y(y) &= \frac{d}{dy} P(Y \le y) \\ &= \frac{d}{dy} F_X (\sqrt{y}) - \frac{d}{dy} F_X (-\sqrt{y}) \\ &= f_X (\sqrt{y}) \frac{1}{2\sqrt{y}} + f_X (-\sqrt{y}) \frac{1}{2\sqrt{y}} \\ &= \frac{1}{\sqrt{y}} \cdot f_X (\sqrt{y}) \qquad (\text{$f_X$κ°€ μš°ν•¨μˆ˜}) \end{aligned}\]


Theorem.

Supp. $X$ has pmf or pdf $f_X (x)$.

Let $Y = g(X)$ where $g$ may not be 1-1.

Assume that the support for $f_X(x)$ can be partitioned into $k$ segments s.t., in each segment, $x_i = w_i(y)$ is 1-1 for $i=1, \dots, k$.

Then,

(1) when $X$ is discrete, $\displaystyle f_Y (y) = \sum^k_{i=1} f_X (w_i (y))$

(2) when $X$ ic continuous, $\displaystyle f_Y (y) = \sum^k_{i=1} f_X (w_i(y)) \cdot \left| w’_i (y) \right|$


μ΄μ–΄μ§€λŠ” ν¬μŠ€νŠΈμ—μ„œλŠ” RV의 momentum인 $E[X]$, $E[X^2]$λ₯Ό μƒμ„±ν•˜λŠ” ν•¨μˆ˜μΈ <MGF; Momemtum Generating Function>에 λŒ€ν•΄ 닀룬닀. 🀩

πŸ‘‰ Momemtum Generating Function